Women's perspectives on human milk banking in Ghana: results from a cross-sectional study - Obeng, Cecilia; Jackson, Frederica; Amissah-Essel, Salome; Nsiah-Asamoah, Christiana; Perry, Cydne A.; Gonzalez Casanova, Ines; Obeng-Gyasi, Emmanuel (Frontiers in Public Health, 2023)
Background: Although political and academic interest exists in Ghana to include human milk banks (HMB) into current maternal and child health programs, efforts to establish a HMB have not yet been subjected to any real empirical inspection with the view toward implementation. Furthermore, views toward the establishment of a HMB in Ghana have not been assessed among Ghanaian women. The aims of the current study were to examine Ghanaian women’s views about HMB, and to investigate women’s willingness to donate to a HMB. Methods: Quantitative and qualitative responses were received from Ghanaian females (n=1270) aged 18+ years. Excluding outliers and missing data (n=321), a final sample of 949 was retained for final analysis. Chi-square tests and logistic regression analysis were computed on quantitative data; Thematic analysis was performed on the qualitative responses. Results: In our sample, 64.7% of respondents indicated that Ghana is ready for a HMB. The majority (77.2%) were willing to donate milk, and 69.4% believed that donating to the HMB would favor their child. The main concerns for the unwillingness to donate excess milk included: (i) the idea of HMBs as strange/bizarre (n=47), (ii) fear of infections (n=15), (iii) religious beliefs (n=9), and (iv) insufficient information (n=24). This study serves as the first step toward the development of a HMB in Ghana. Conclusions: Overall, Ghanaian women support the building of a HMB to enhance infant nutrition and reduce childhood morbidity and mortality.